Policy measures to apply the Whole System Approach (WSA) in energy infrastructures - Gert Brunekreeft; Dierk Bauknecht; Martin Palovic; Anna Pechan; Franziska Flachsbarth; Matthias Koch (Constructor University Bremen, Bremen Energy Research (BER), 2024)
Following liberalization and especially the energy transition, energy infrastructures are developing rapidly and significantly. Electricity networks are expanded to facilitate connection of renewable energies and new load such as heat pumps and electric mobility. On the one hand, gas networks are preparing for a phase-out and, on the other hand, for a possible repurposing for transportation of hydrogen. At a communal level, the heat supply moves towards heat pumps and district heating, both in turn affecting electricity and gas infrastructure. Lastly, infrastructure for hydrogen and CO2 for CCS are being developed. These developments affect various stages within the energy sectors. These simultaneous and interactive developments require coordination between and within the different energy infrastructure. Improving the coordination of energy infrastructures has been coined Whole System Approach (WSA). In this report, we examine approaches and policy measures for applying the Whole System Approach.
Keywords: 330